Pengembangan Bahan Ajar Pendidikan Jasmani untuk Anak Usia Dini Berbasis Tematik - Wijaya Kuswanto, Cahniyo; Dinda Pratiwi, Dona (Al-Athfal: Jurnal Pendidikan Anak, 2020)
This research aims to develop thematic-based physical education teaching materials that aim to introduce motions to children and help teachers as a guide to teach physical education. The following teaching material contains physical games that are integrated with the theme and are equipped with ways to maintain cleanliness (both for the self and the environment) and handling injuries during playtime. The research method is Research and Development (R&D), with the ADDIE (Analysis, Design, Development, Implement, dan Evaluation) model involving several PAUD teachers in the Lampung Province. The results of the research from the validation of the material experts found an average of 3.8, which means the product is very feasible to use. The validation of media experts gets an average of 3.09, which means that the media is appropriate to use. Ratings from users on small-scale trials get an average of 2.60 which means they generally agree on the usage of said materials. Large-scale trials get an average value of 3.45, which means that they strongly agree on its usage. These results indicate that the thematic-based physical education teaching materials are specifically "very feasible to use" and it is expected for the teachers to use them as early childhood learning materials.